Evaluation and comparison of modifications in the kato-katz thick smear technique for the detection of hookworm ova. - Sripawit, Anchalee
Modifications of the Kato-katz' method were developed and evaluated. It was shown that formalin can significantly prolong the integrity of hookworm ova although the characteristics of the hookworm egg has changed and is quite difficult to recognize as the aging of preparation progresses. A solution containing 10 formalin is selected since it has the lowest percentage of trial formalin, has less toxic effects and is less expensive. This solution also gives a similar egg-counting result as the original Kato-katz solution at 30 minutes and 1 hour. Compared to the Stoll's method, it gives higher sensitivity especially in light infections. Optimum clearing time is between 30 minutes and 1 hour. The modified technique is very useful qualitatively for mass surveys and the evaluation of control programs.